Sustainability in the commercial sector – the international trend of the shorter supply chains - Henrietta Nagy; György Iván Neszmélyi; Gabriella Soós; Tamás Tóth (Marine Development)
Abstract Since the beginning of 2020, the world economy’s globalization process has undergone marked changes. The COVID-19 pandemic, the energy crisis, inflation, and the Russia–Ukraine conflict disrupted and interrupted the existing supply chains. Large geographical distances now mean increased transport costs and serious security risks in some cases. The latter represents the specific risks of war and the unexpected failure of even one or two of the large number of components required for manufacturing processes, which can cause serious problems in production and sales. Consequently, supply chains are shortening worldwide. This study presents the contradictory characteristics of this trend through bibliographic research and the introduction of specific cases. The results underline that reorganizing and redesigning large companies’ production and logistics systems is not automatic, and national governments are important in this multifaceted process. This latter intention can be seen in the domestication of new industries and the repatriation of industries previously outsourced abroad, typically to East Asia. Regarding logistical aspects, safety and sustainability are also strengthened by shortening supply chains, which increases the importance of local producers and markets.